2015
DOI: 10.4103/1117-6806.162575
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic evaluation of upper and lower gastro-intestinal bleeding

Abstract: Introduction:A myriad of pathologies lead to gastro-intestinal bleeding (GIB). The common clinical presentations are hematemesis, melena, and hematochezia. Endoscopy aids localization and treatment of these lesions.Aims:The aim was to study the differential diagnosis of GIB emphasizing the role of endoscopy in diagnosis and treatment of GIB.Patients and Methods:A prospective study of patients with GIB referred to the Endoscopy unit of two health facilities in Port Harcourt Nigeria from February 2012 to August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Hemorrhoids are a leading cause of lower gastrointestinal bleeding with a high impact on quality of life. [12] The pathophysiology is multifactorial including: sliding anal cushion; hyperperfusion of hemorrhoid plexus; vascular abnormality; tissue inflammation; and internal rectal prolapse (rectal redundancy). [345] The predisposing conditions to increased incidence of symptomatic hemorrhoids include state of elevated intra-abdominal pressure such as pregnancy and straining.…”
Section: Introductionmentioning
confidence: 99%
“…Hemorrhoids are a leading cause of lower gastrointestinal bleeding with a high impact on quality of life. [12] The pathophysiology is multifactorial including: sliding anal cushion; hyperperfusion of hemorrhoid plexus; vascular abnormality; tissue inflammation; and internal rectal prolapse (rectal redundancy). [345] The predisposing conditions to increased incidence of symptomatic hemorrhoids include state of elevated intra-abdominal pressure such as pregnancy and straining.…”
Section: Introductionmentioning
confidence: 99%
“…Similar reports are documented from Europe and North America [ 3 , 6 , 19 ]. In an earlier report from our center involving half of the present study population, gastritis/erosions (39%), peptic ulcer disease (13%), and oesophageal varices (4.3%), among others, were reported as common causes of UGIB diagnosed by endoscopy [ 20 ]. The trend of UGIB may have changed due to increased patient referrals.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies confirmed the association of anorectal varices with portal hypertension in cirrhotic patients (Li et al, 2015). However, later studies showed the absence of differences in the hepatic venous pressure in cirrhotic patients with and without anorectal varices (Ray-Offor et al, 2015). Sinusoids are hyperperfused and overloaded, whereas connective tissue loses its capacity to support the vascular network and impedes venous return (Kuivaniemi et al, 2019).…”
Section: Sliding Anal Cushionsmentioning
confidence: 99%
“…Increased pressure on anorectal vascular plexus. Increased pressure on anorectal vascular plexus is a chronic rise in intraabdominal pressure when even cough in combination with the absence of valves within rectal veins can limit venous drainage from sinusoids during defecation, leading to abnormal dilatation of the arterio-venous anastomoses in internal haemorrhoidal plexus (Li et al, 2015;Ray-Offor et al, 2015). Defecation habits change over time to sitting down instead of squatting.…”
Section: Sliding Anal Cushionsmentioning
confidence: 99%